Pengaruh Dosis KNO3 Terhadap Pertumbuhan dan Hasil Bawang Merah di Tanah Gambut - Maulidi, Maulidi; Warganda, Warganda; Bandem, Putu Dupa (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2023)
The production of shallots (Allium ascalonicum L.) needs to be improved. Potassium is an essential nutrient needed by shallots. The research aims to obtain the best dosage of KNO3 for red growth and yield in peat. The research was conducted in Rasau Jaya, Kubu Raya Regency. The study was carried out for 7 months. The design used was a Randomized Block Design (RBD) consisting of 5 settings and 5 blocks, containing 6 plant samples. The five treatments were KNO3 (K) fertilizer dosage consisting of k1 = 0 g / plant, k2 = 3 g / plant, k3 = 6 g / plant, k4 = 9 g / plant and k5 = 12 g / plant. Observation variables were number of leaves per clump, tuber diameter per clump, number of tubers per clump, fresh weight of tubers per clump and tuber dry weight per clump. The analysis of variance showed that tretments of dosage of KNO3 were significantly effected to all observation variables. The doseage of KNO3 of 9 g / plant is the best effect on growth and yield of shallots on peat.